PENGHIMPUNAN DAN PENGELOLAAN WAKAF UANG DI LEMBAGA GERAKAN WAKAF INDONESIA (GWI) - Dinda Rizky Meidiana; Norma Rosyidah (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
Waqf has become a popular sharia economic instrument in recent years. Waqf itself is one of the human fields for productive charity. The Indonesian Waqf Movement is one of the nazir institutions that carry out cash waqf collection activities. This institution was founded in 2018 and is located in the Gedangan Sidoarjo area. This paper aims to describe the reality of cash waqf management carried out by Gerakan Wakaf Indonesia. The method used in this study is a descriptive analysis using a case study approach that describes field events regarding the management of cash waqf in nazir institutions. The results of this study indicate that the management of cash waqf carried out by GWI is following existing regulations ranging from laws to regulations issued by Badan Wakaf Indonesia. The collection of cash waqf in the Indonesian Waqf Movement uses an indirect method with an introduction, approach, and collection strategy. This research is expected to be able to add to the reader's literature regarding the process of managing cash waqf in Gerakan Wakaf Indonesia. Keywords: Cash Waqf, Collection, Management References Direktorat Pemberdayaan Wakaf. Tanya Jawab Tentang Wakaf Uang, n.d. Gerakan wakaf. “Badan Wakaf Indonesia Untuk Mempresentasikan Program Kerja GWI Dalam Rangka Pengajuan Sebagai Nazir Wakaf Uang,” 2019. Accessed February 12, 2022. https://gerakanwakaf.id/2019/10/17/gerakan-wakaf-indonesia-hadir-memenuhi-undangan-badan-wakaf-indonesia-untuk-mempresentasikan-program-kerja-gwi-dalam-rangka-pengajuan-sebagai-nazir-wakaf-uang/. Huda, Miftahul. “Model Manajemen Fundraising Wakaf.” AHKAM : Jurnal Ilmu Syariah 13, no. 1 (February 1, 2013). Accessed November 18, 2022. http://journal.uinjkt.ac.id/index.php/ahkam/article/view/948. Ibu Novita Anggraini. “Wawancara,” December 6, 2022. Komisi Fatwa Majelis Ulama Indonesia (MUI). Fatwa DSN-MUI Tentang Wakaf Uang, 2002. Lubis, Suhrawardi K., dkk. Wakaf Dan Pemberdayaan Umat. Jakarta: Sinar Grafika, 2010. Purwanto April. Manajemen Fundraising Bagi Organisasi Pengelola Zakat. Yogyakarta: Teras, 2009. Retno Ika Lestari Widianti. “Potensi Wakaf Uang Tingkatkan Kesejahteraan Pasca Pandemi.” Badan Wakaf Indonesia. Last modified 2022. Accessed November 18, 2022. https://www.bwi.go.id/7851/2022/03/17/potensi-wakaf-uang-tingkatkan-kesejahteraan-pascapandemi/. Siti Nuralamah. “Strategi Penghimpunan (Fundraising) Dan Pengelolaan Wakaf Pada Yayasan Pendidikan Dan Sosial Islam (Yapsi) Darul Amal - Sukabumi.” Skripsi, Universitas Islam Negeri Syarif Hidayatullah, 2017. Suryadi, Nanda, and Arie Yusnelly. “Pengelolaan Wakaf Uang Di Indonesia” 2 (2019): 10. Peraturan Badan Wakaf Indonesia (BWI) Nomor 01 Tahun 2009, n.d.